2019
DOI: 10.14735/amko2019170
|View full text |Cite
|
Sign up to set email alerts
|

Association of TNF-α -308G>A Polymorphism with Susceptibility to Cervical Cancer and Breast Cancer – a Systematic Review and Meta-analysis

Abstract: Background: To date, several studies have been carried out on the association of TNF-α-308G>A with the risk of cervical cancer (CC) and breast cancer (BC). However, their conclusions were not consistent. Thus, we performed a comprehensive meta-analysis to evaluate the association more precisely from all eligible case-control studies. Methods: We searched the PubMed, Google Scholar and Cochrane Library databases systematically to identify relevant studies up to 1 February 2019. The pooled odds ratio (OR) with 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Studies have shown that in addition to cancerous cells in tumor tissue, 80% of cells belong to stromal cells and inflammatory cells. These stromal cells play an important role in the development of tumor cells, and cytokines produced by stromal cells also form a complex network of tumor regulation [ 14 , 15 ]. The results of this study showed that the level of serum inflammatory factors (TNF- α ) in the breast group patients was significantly higher than that in the benign breast group and the healthy group, and with the aggravation of the disease, the serum TNF- α level gradually increased.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that in addition to cancerous cells in tumor tissue, 80% of cells belong to stromal cells and inflammatory cells. These stromal cells play an important role in the development of tumor cells, and cytokines produced by stromal cells also form a complex network of tumor regulation [ 14 , 15 ]. The results of this study showed that the level of serum inflammatory factors (TNF- α ) in the breast group patients was significantly higher than that in the benign breast group and the healthy group, and with the aggravation of the disease, the serum TNF- α level gradually increased.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of publication bias in a meta-analysis is always a concern, especially when the number of incorporated studies is small (42)(43)(44) . Although, large number of studies included in this meta-analysis, publication bias have distorted our results.…”
Section: Discussionmentioning
confidence: 99%
“… 6 IL1R2 and TNF genetic polymorphisms increase the risk of cervical cancer in Uygur women in China. 7 , 8 The polymorphism in the CCR5 promoter region can affect the occurrence of cervical cancer in the Chinese Han population. 9 TP53 Codon 72 polymorphism was reported to be also associated with cervical cancer.…”
Section: Introductionmentioning
confidence: 99%